2018
DOI: 10.1186/s12887-018-1002-5
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein for late-onset sepsis diagnosis in very low birth weight infants

Abstract: BackgroundLate-onset sepsis in very low birth weight (VLBW) infants is a diagnostic challenge. We aimed to evaluate the diagnostic utility of the C-Reactive protein (CRP) and the complete blood count (CBC) for late-onset sepsis in VLBW infants.MethodsIn a 5-year retrospective cohort of 416 VLBW infants born at less than 1500 g, there were 590 separate late-onset sepsis evaluations. CRP and CBC were drawn at time of initial blood culture (T0), at 16–24 h (T24) and 40–48 h (T48) after. The positive cut-off value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 31 publications
0
28
0
2
Order By: Relevance
“…As the level of CRP synthesis reflects the intensity of the inflammatory process, it is used as one of the clinical markers of infectious and inflammatory diseases, including sepsis 59,60. It was demonstrated that high concentrations of CRP in the development of sepsis indicate unfavorable prognosis 61. Therefore, rats susceptible to hypoxia are characterized by more pronounced inflammatory reaction in response to the administration of the LPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the level of CRP synthesis reflects the intensity of the inflammatory process, it is used as one of the clinical markers of infectious and inflammatory diseases, including sepsis 59,60. It was demonstrated that high concentrations of CRP in the development of sepsis indicate unfavorable prognosis 61. Therefore, rats susceptible to hypoxia are characterized by more pronounced inflammatory reaction in response to the administration of the LPS.…”
Section: Discussionmentioning
confidence: 99%
“… 59 , 60 It was demonstrated that high concentrations of CRP in the development of sepsis indicate unfavorable prognosis. 61 Therefore, rats susceptible to hypoxia are characterized by more pronounced inflammatory reaction in response to the administration of the LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Use of the combination of CRP and CBC for discontinuation of antibiotics at 36 h after LOS work-up has previously been suggested by Beltempo et al ( 31 ). CBC abnormalities in this study were abnormal white blood cell count, thrombocytopenia or a high immature neutrophil count.…”
Section: Discussionmentioning
confidence: 98%
“…As the level of CRP synthesis reflects the intensity of the inflammatory process, it is used as one of the clinical markers of infectious and inflammatory diseases, including sepsis [46, 47]. It was demonstrated that high concentrations of CRP in the development of sepsis indicate unfavorable prognosis [48]. According to the literature, the main inducer of CRP gene expression is IL-6, with IL-1 enhancing the effect during the acute phase of an inflammatory/infectious process [49].…”
Section: Discussionmentioning
confidence: 99%